SOCIALIZATION OF DOMESTIC WASTE REDUCTION PROGRAM UTILIZING REUSABLE PACKAGING AND WASTE MANAGEMENT THROUGH COMPOSTING - Bintang Ekananda; Rian Sumendar (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The alarming rise in uncollected waste volume in Jakarta, Indonesia necessitates an innovative, community-centered approach to waste reduction. This report details the socialization and training program initiated in the Cilandak region, South Jakarta, focusing on waste prevention at the source through a partnership with the startup company Alner. The program encourages the use of reusable packaging for everyday products and promotes composting organic waste. Lectures and practical demonstrations were employed to educate residents about the waste management hierarchy of reduction, reuse, and recycling. Over 50 participants adopted reusable Alner-packaged products, and several engaged in on-site composting. The initiative was successful in fostering a better understanding of proactive waste management strategies and the financial benefits of a circular economy. Given the positive feedback, the program may be considered for replication across other Jakarta regions to amplify its impact on waste reduction.